Elementy teologii duchowości w „Collectanea Theologica” 1920-2020 - Tatar, Marek (Collectanea Theologica, 2020)
The development of theology over the centuries of the Church’s life and activity is accomplished through publications. They express the theologians’ positions, opinions and hypotheses. Among Polish theological journals, “Collectanea Theologica”, which has its origins in Lviv (“Przegląd Teologiczny”), plays a special role. Though it is connected with the Warsaw theological environment, it not only covers Poland but also goes beyond its borders, as evidenced by the foreign publications and foreign-language authors. Undoubtedly, this journal has become a very serious and rich source of and platform for the development of the theology of spirituality. Its existence is connected with the independence of this branch of the theology, and therefore from the beginning of its existence we find in the journal highly valuable and serious materials on spirituality. The analysis of the publications, which are the result of research conducted over a hundred years, allows us to conclude that we are dealing with an unusual and multidirectional wealth. It should be stated that the publications present an interdisciplinary nature of the research conducted. The study outlines the main directions of the development of the theology of spirituality and their documentation. It can be said that these publications reflect theological trends in the universal Church. Both the documents of the Church and of the popes as well as the events became an inspiration for the authors. Historical, social and even political events were not without their significance and influence. Of particular importance is the development of native Polish theology, having its own specificity and contributing richly to the life of the whole universal Church. We define such a achievement as the “Polish school of spirituality”.